Bis(benzo-15-crown-5-κ5O)barium tetrakis(isothiocyanato-κN)cobaltate(II) - V. Ravisankar; V. Ramesh; M. Krishnamohan; B. Gunasekaran; T. C. Sabari Girisun (IUCrData, 2021)
The title compound, [Ba(C14H20O5)2][Co(NCS)4], is formed by discrete anions and cations. The molecular packing is controlled by weak C—H...π interactions.